The gateware calibration unit for the KM3NeT telescope. (29th October 2021) - Calvo, D.; Real, R.; Amaro, A.; van Beveren, V.; Chiarusi, T.; Mastroianni, S.; Musico, P.; Pellegini, G.; Jansweijer, P.; Colonges, S.; Bozza, C.; Nicolau, C.; et al.
Abstract: The KM3NeT collaboration is currently deploying the first detection units of a neutrino observatory in the Mediterranean Sea, which, once completed, will be equipped with thousands of so-called digital optical modules. In addition to the detection units KM3NeT has designed an independent calibration unit, housing a set of calibration instruments, including e.g. an acoustic beacon and a laser beacon. The calibration unit and the embedded software developed to operate it are presented here.